Evolution of Micro-pore structure in saline agricultural soil driven by sand addition of specific particle sizes and its regulation mechanism on water and salt transport - Yi Meng; Shuanhu Li; Chi Li; Bing Zhang; De Yao; Xiaorong Wang (Journal of Contaminant Hydrology, 2026)

High-speed air circulation preserves curcumin bioactivity and enables pH-dependent intestinal release in oyster-based functional foods for IBD dietary intervention - Shuang Gao; Xue Jiang; Yi Rong; Huanhuan Chi; Ci Song; Shujia Wang; Ying Li; Jingjing Chen; Lida Yang; Huawei Ma (Food Research International, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Multiplexed EDL-FET biosensor with tannic acid stabilization for simultaneous p-Tau217 and Aβ42/Aβ40 detection in plasma and whole blood from stroke patients - Shang-Chi Chien; I-Yin Chang; Yong-Chuan Chen; Yi-Zhen Lai; Yu-Fang Chen; Pei-Lun Sun; Bor-Ran Li; Yu-Lin Wang; Jung-Chih Chen (Analytica Chimica Acta, 2026)

Functional characterization of the Cbr1 gene in regulating alkaline tolerance in grass carp - Jianbo Zheng; Yi Xu; Qi Chen; Fei Li; Shili Liu; Chao Zhu; Shun Cheng; Wenping Jiang; Meili Chi; Junzhi Luo; Caiyan Li; Xiaohui Xu; et al. (Aquaculture, 2026)

Targeted isolation of previously undescribed fortunefuroic acid-type triterpenoids from Keteleeria pubescens using 1H NMR/LC-PDA-MS and assessment of ACL Inhibition - Chun-Jing Chi; Ze-Yu Zhao; Yi Zang; Cong Li; Jia Li; Dong Huang; Peng Sun; Juan Xiong; Yeun-Mun Choo; Jin-Feng Hu (Phytochemistry, 2026)

Integrated geophysical insights into the structural controls on geothermal systems in the Tatun Volcano group, northern Taiwan - T. Lan-Chi Nguyen; Wen-Jeng Huang; Chien-Chih Chen; Chi-Shu Yen; Yi-Heng Li; Horng-Yuan Yen (Geothermics, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

Depth heterogeneity within surface soils substantially affects microbial abundance, diversity, and co-occurrence patterns - Guanyu Chai; Yuan Du; Zelin Wang; Kaifang Liu; Yuan Chi; Yi Duan; Shuo Ma; Xin Hu; Rongxiao Che; Jianxing Li; Wenjun Liu; Dong Liu (Journal of Soils and Sediments, 2026)

Influence of roughness on overtopping flow at a dike using deep learning-based video measurement techniques - Weiqiu Chen; Xinrui Sun; Chi Zhang; Yi Xu; Shanhang Chi; Titi Sui; Yuan Li; Fei He; Jinhai Zheng (Ocean Engineering, 2026)

From built-in LiDFP to high-stability interface: A targeted and persistent multistage strategy for lithium-rich cathode - Jin Zhu; Xiaosong Zhang; Denghui Ma; Lei Zhang; Yiyao Xiao; Keyu Zheng; Jiamin Duan; Shunjie Xu; Longhao Cao; Yinghui Li; Guanghua Guo; Xiuxia Zuo; et al. (Chemical Engineering Journal, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Withanolides from Datura stramonium: two unprecedented B-ring-seco derivatives and anti-inflammatory active analogues - Juan Pan; Gang-Tao Bu; Si-Yi Wang; Jia-Tong Wu; Meng-Meng Li; Wei Guan; Qing-Shan Chen; Li-Li Zhang; Xiao-Chi Ma; Hai-Xue Kuang; Yan Liu (Phytochemistry, 2026)

Enhancing starch-lipid complexes and digestive resistance in rice with curcumin-loaded self-emulsifying delivery systems via microwave/ultrasound-assisted hydrothermal treatments - Tsung-Chi Liu; Yi-Chan Chiang; Po-Hsien Li; Po-Yuan Chiang (Food Hydrocolloids, 2026)

Rice-crab co-culture mitigates reactive gaseous N losses and increases economic benefits - Feng Zhang; Guimin Xia; Yuanze Qiu; Hongwei Han; Haixia Liu; Benji Yi; Bohao Li; Daocai Chi; Taotao Chen (Field Crops Research, 2026)

Comprehensive phylogenomic analyses of ciliated protists with a revised classification of the phylum Ciliophora (Eukaryota, Alveolata) - Yurui Wang; Ying Yan; Zhenzhen Yi; Yan Zhao; Qianqian Zhang; Yong Chi; Tengyue Zhang; Weiwei Liu; Mingjian Liu; Borong Lu; Mingzhen Ma; Wenbao Zhuang; et al. (Science China Life Sciences, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Genomic insights and vaccine evaluation of a virulent MLST ST234 Bacillus cereus infecting Asian sea bass (Lates calcarifer) - Li-Wu Cheng; Qiong-Yi Huang; Nopadon Pirarat; Abisheik Rajandran; Sayuj Poudyal; Pei-Chi Wang; Shih-Chu Chen (Fish & Shellfish Immunology, 2026)

Response of a heterotrophic denitrification system to aminopyralid stress: a comparative analysis of nitrogen removal performance and microbial community structure - Chi Sun; Yi Han; Jianbing Zhang; Haibo Li; Runnan Zhao (Bioresource Technology Reports, 2026)

Molnupiravir: A Prodrug of the Ribonucleoside β‐D‐N4‐Hydroxycytidine Triphosphate Inhibits the Propagation of Nervous Necrosis Virus in Grouper Brain Cells - Chen‐Kung Chi; Vertika Bajpai; Chen‐Hung Li; Hsin‐Yi Tsai; Chien‐Wen Chen; Chao‐An Cheng; Hsia‐Wei Liu; Chi‐Yao Chang (Journal of Fish Diseases, 2026)
Nervous necrosis virus (NNV) is the causative agent of viral nervous necrosis, otherwise known as viral encephalopathy and retinopathy in larval and juvenile marine fish worldwide. The pandemic outbreaks have caused nearly 100% mortality in hatcheries, leading to significant economic losses in the aquaculture industry. Since NNV attacks the insufficient immune competence fish at early developmental stages, there is an urgent need for effective antiviral drugs. Several nucleoside analogues, including Molnupiravir, have been developed to target viral RNA‐dependent RNA polymerase (RdRp). This study examines the antiviral activity of Molnupiravir against NNV isolated from giant grouper (GG), Epinephelus lanceolatus (Bloch), using grouper brain (GB) cells as an infection model. The inhibition concentration for 50% of maximal effect (EC 50 ) of Molnupiravir on GGNNV propagation in GB cells was determined as 1.87 μM. Surprisingly, the titre of GGNNV reduced 50,000 at 100 μM of Molnupiravir treatment at 4‐day post‐infection, whereas treatment with 200 μM of Molnupiravir resulted in a 10 5 reduction in viral titre. The inhibition of viral replication and translation was further examined using RNA‐fluorescence in situ hybridization (FISH) and immunocytochemistry detection, respectively. Moreover, administration of 100 μM Molnupiravir at early time 0 hpi resulted in a dramatic decrease in viral load, reducing cell‐associated virus by approximately 4000‐fold and released virus by 6000‐fold. Finally, the molecular docking simulation model supports the interaction between NHC‐TP and GGNNV RdRp for the successful therapeutics. These results demonstrated that Molnupiravir is a very effective therapeutic drug for controlling viral nervous necrosis caused by NNV infection.

Green synthesis of glycerol carbonate from glycerol and CO2 using a polymeric ionic liquid catalyst: An experimental and theoretical study - Yi-Lin Lee; Yu-Chi Kao; He-Xiang Xu; Shun Tsunekawa; Masaaki Yoshida; Yi-Pei Li; Chechia Hu (Journal of Cleaner Production, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Thermal runaway behaviour induced by localised aluminium-water reaction at low temperature - Hai-Fang Mao; Jia-Wei Fang; Yi-Kang Deng; Jun Zhang; Yan-Li Zhao; Yao Feng; Min Xiong; Hui-Ting Gu; Xiao Feng; Jian-Hao Fang; Jian-Hua Chen; Chi-Min Shu; et al. (Chemical Engineering Journal, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Development of interfacial oxygen micro-nanobubble technology for hypoxia remediation: Machine-learning assisted optimization and mechanistic insights into sustained oxygen release - Xinyan Xiong; Yi Li; Ying Zhou; Yifei Gao; Chi Zhang (Water Research, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Analysis of the resistance and flow characteristics of a square diffuser under adjacent influence conditions based on design of experiments - Haimeng Li; Wei Xu; Ran Gao; Xinyu Zhang; Chi Zhang; Yan Tian; Yi Wang; Ruoyin Jing (Building and Environment, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Ion-dipole interactions regulated interface for stable high-depth of discharge Zn anode - Pengyan Jiang; Xiaobin Hui; Yuyang Yi; Renjie Li; Jingya Yu; Feiyang Chen; Liucheng Cao; Chi Fai Cheung; Kai Qi; Bao Yu Xia; Zheng-Long Xu (Chemical Engineering Journal, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

Determination of dissolved inorganic carbon export and the controlling factors in small mountainous Rivers, Taiwan - Man-Ching Choi; Pei-Hao Chen; Chi-Wang Tsui; Jr-Chuan Huang; Jun-Yi Lee; Li-Chin Lee (Journal of Hydrology, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Full-genome sequence of a novel potyvirus infecting Sauropus androgynus - Li-Juan Zhu; Shulian Su; Jingke Li; Yubin Chi; Yankun Zhu; Xing Chen; Lan-Yi Su; Juncheng Zhang; Zhongtian Xu (Virus Genes, 2025)

Marine algae and their bioactive compounds as novel modulators for mitochondrial quality control: from mechanism to therapeutic potential - Chi Zhang; Ling Yuan; Jingjing Li; Doudou Lu; Yuhua Du; Yi Nan (Frontiers in Marine Science, 2025)
Mitochondrial Quality Control (MQC) is the core mechanism for ensuring mitochondrial quality and maintaining cellular function. Marine algae and their bioactive compounds represent a huge treasure trove of natural medicines. In recent years, research on the regulation of mitochondrial biogenesis, mitochondrial dynamics, mitophagy, and mitochondrial protein balance by marine algae has continuously emerged, and their mechanisms of action have gradually become clearer. Bioactive compounds are the material basis for marine algae to exert this regulatory function. Based on their chemical structures, they can be classified into types such as marine algal polysaccharides, marine algal carotenoids, marine algal proteins, and marine algal peptides. Based on the analysis of the chemical structures of these compounds, we believe that structural differences, including planarity, degree of sulfation, and stereoisomerism, may help explain their regulatory effects on MQC. Furthermore, numerous scholars have demonstrated through preclinical studies, using animal or cell models, that marine algae and their bioactive compounds can improve muscle function, treat tumors, type 2 diabetes mellitus, and nervous system diseases, among other effects, by regulating MQC. Currently, this interdisciplinary field holds significant potential for development. This review primarily incorporates literature published between 2019 and 2025 that is highly relevant to the mechanisms of MQC regulation by marine algae and their bioactive compounds. It analyzes the latest research progress from three dimensions: mechanisms of action, molecular structures, and therapeutic applications. Furthermore, it identifies potential challenges and future research directions in the field, aiming to provide support for future drug development and treatment strategies.

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Feasibility assessment of online coal quality monitoring based on concentrating photothermal rapid combustion: Insights from neural network and explainability analysis - Ying Wu; Pengfeng Yu; Jun Xu; Hanjian Li; Kai Xu; Huanying Chi; Long Jiang; Yi Wang; Sheng Su; Song Hu; Jun Xiang (Fuel, 2025)

Collagen peptides from Skipjack tuna (Katsuwonus pelamis) bones: Composition, characterization, and mechanism of high-fat diet-induced NAFLD amelioration - Yu-Lin Jiang; Shuang-Yi Zhang; Bin Wang; Yu-Hui Zeng; Li Xu; Chang-Feng Chi (Food Research International, 2025)

Environmental nanotechnology for dual-functional water remediation: Mg-doped magnetic biochar overcomes recyclability-adsorption trade-off in nutrient recovery - Qi Wu; Yi Zhao; Xiaolong Liu; Daocai Chi; Haifeng Liu; Wei Chen; Hongbo Zhang; Yanqi Li; Ye Jin; Qingliang Liu; Yang Sun (Journal of Environmental Chemical Engineering, 2025)

Nano architectonics via in situ growth of MIL-101(Fe) on modified sugarcane bagasse for selective capture of glyphosate from aqueous solution - Ru-yi Zhou; Ming-hua Liu; Yun Xiao; Yu Qin; Bo Zuo; Muhammad Akhtar Abbas; Jun-xia Yu; Xiao-di Li; Yue-fei Zhang; Ru-an Chi (Journal of Environmental Chemical Engineering, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Changes in the physiological indicators and gene expression for grass carp (Ctenopharyngodon idella) in response to alkaline stress - Qi Chen; Jianbo Zheng; Yi Xu; Fei Li; Shili Liu; Wenping Jiang; Meili Chi; Shun Cheng; Haiqi Zhang (Aquaculture International, 2025)

Resolving the Genetic Divergence and Population Structure in the Circumpolar Ophiuroid Ophiura sarsii Complex - Yi‐Xuan Li; Sophia Nazarova; Jack Chi‐Ho Ip; Evgeny Genelt‐Yanovskiy; Ting Xu; Yue Dong; Jian‐Wen Qiu; Xue‐Lei Zhang; Qin‐Zeng Xu (Journal of Biogeography, 2025)
Aim The presence of cryptic species causes significant challenges to biodiversity assessment and biological resources management. Here, we investigate the genetic structure and biogeographical patterns of a complex ophiuroid species as a case study. Location Yellow Sea and Funka Bay in the Western Pacific Ocean, Bering Sea in the Arctic Ocean and Barents Sea in the Atlantic Ocean. Taxon The circumpolar ophiuroid Ophiura sarsi i , a common benthic species across the Arctic seas, has at least two cryptic lineages. Methods To better understand the genetic structures and the underlying evolutionary processes in the O. sarsii species complex, we compared the genome‐wide single nucleotide polymorphism (SNP) data and COI of five geographical populations across the northern Pacific, Arctic and Atlantic Oceans using the 2b‐RAD sequencing approach. Results Results clearly showed three highly diverged evolutionary lineages: northern Pacific lineage ( O. sarsii vadicola ), Pacific‐Arctic lineage ( L A ) and Atlantic lineage ( L B ). The divMigrate analysis revealed significant gene flow within O. sarsii vadicola populations and O. sarsii L A populations, but no cross‐species gene flow. Demographic analysis was used to estimate their historical divergence, in which the differentiation of O. sarsii vadicola predated that of the other two lineages of O. sarsii . Molecular dating resulted in an estimation of their divergence events between 3.88 and 1.67 Ma at Pliocene–Pleistocene using COI . Functional analysis revealed several enriched signalling pathways, potentially involved in ophiuroids' environmental adaptation. Main Conclusions Our study suggests three lineages of the cryptic species O. sarsii could split into at least two genetic species, including O. sarsii vadicola , North Pacific–Arctic and Atlantic O. sarsii . The hidden evolutionary trajectory is uncovered for the O. sarsii complex, shaped by paleoclimate and ocean currents. We emphasise the need for genome‐wide SNP applications to understand the ophiuroid biodiversity and contribute to conservation in the Pacific–Arctic region.

ORMCKB: A Knowledge Database for Personalized Medicine in Deciphering the Oral Microbiome-Disease Axis - Yutao Wu; Yi Zhou; Wenjing Shi; Siyu Zhou; Min Jiang; Ke Shen; Xingyun Liu; Xiaoyu Li; Jiao Wang; Chi Zhang; Bairong Shen; Weidong Tian (Interdisciplinary Sciences: Computational Life Sciences, 2025)

A selenium nanozyme: Light/mercury dual-enhanced oxidase mimicry for simultaneous ultra-sensitive detection and efficient removal of mercury ions, and superior photocatalytic bacterial disinfection - Yu Shi; Dong-hui Li; Chi Zhang; Zheng-ren Wang; Yi-ran Wang; Ru-kang Chen; Yen-ho Chu; Yu-gang Shi; Rammile Ettelaie; Qing Gu (Water Research, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Reanalysis-data-based approach to generate urban local weather data to support building energy design in a tropical climate - Xing Zheng; Naika Meili; Shuyang Li; Huanhuan Wang; Lei Xu; Zhen Han; Martín Mosteiro-Romero; Yi Wu; Da Yan; Dengkai Chi; Guanli Feng; Rudi Stouffs (Sustainable Cities and Society, 2025)

Combustion inhibition and promotion mechanisms of C3F7COC2F5 in H2-CH4-air mixture flames - Nan Luo; Hongfu Mi; Xinyu Wang; Liang Shu; Wenhe Wang; Hang Yi; Haoliang Zhang; Peng Shao; Shuo Wang; Li-Huan Zhu; Chi-Min Shu (Process Safety and Environmental Protection, 2025)

Diterpene-phenylpropanoid hybrids and structurally diverse diterpenoid monomers from the endangered conifer Podocarpus annamiensis and their bioactivities - Chi Song; Ze-Yu Zhao; Yi Zang; Jia Li; Yeun-Mun Choo; Haibo Wang; Guangyao Mei; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2025)

Innovative application of recyclable magnetic LDO beads for enhancing the remediation of Cd and Pb contamination and the humification during composting - Hongjuan Jiang; Zhigang Yi; Yaoning Chen; Yuanping Li; Mengyang Zhao; Jun Wang; Yihuan Liu; Xuyang Jia; Mengwei Luo; Yaoqin Nie; Nianping Chi (Journal of Hazardous Materials, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

The conservation of migratory shorebirds needs to account for the different habitat selection patterns across species and between day and night - Shen Zhang; Xiaotong Ren; Ziyin Xiong; Tao He; Kar-Sin Katherine Leung; Wenjie Xue; Li Tian; Lifeng Zhuang; Yi-Chien Lai; Chia-Hsiang Lin; Chi-Yeung Choi (Biological Conservation, 2025)

Assessing landslide risks across varied land-use types in the face of climate change - Chi-Wen Chen; Yu-Shiang Tung; Fang-Yi Chu; Hsin-Chi Li; Yung-Ming Chen (Landslides, 2025)

Air quality and mental health amid COVID-19: a prospective population-based analysis of the mediating role of daily routine disruptions - Selina Kit Yi Chan; Crystal Jingru Li; Percy Poo-see Tse; Evon Lam Wong; Anan Wang; Huinan Liu; Stevan E. Hobfoll; Chi Yung Jim; Wai Kai Hou (Air Quality, Atmosphere & Health, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Biopolymer-amended geosynthetic clay liners for landfills and contaminated sites: Gas and hydraulic performance - Ying-Zhen Li; Heng Zhuang; Ji-Ying Fan; Wei-Yi Xia; Jia-Lei Wan; Chi Che; Yan-Jun Du (Environmental Research, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Enhanced expression of glycolysis regulators KmGcr1p and KmGcr2p in Kluyveromyces marxianus: An efficient strategy for high-temperature ethanol production from inulin - Lan Xu; Hui-Min Wang; Feng-Yi Li; Wen-Hui Zhao; Dan Yue; Zhen-Ming Chi; Guang-Lei Liu (Bioresource Technology, 2025)

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XLIV. Integrated NMR/EI-MS/LC-PDA-ESIMS approach for dereplication and targeted isolation of fortunefuroic acids from Keteleeria fortunei across diverse geographical origins - Ze-Yu Zhao; Zhe-Lu Jiang; Ying-Peng Tong; Chun-Jing Chi; Yi Zang; Yeun-Mun Choo; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Simultaneous dyeing and wastewater treatment in one bath by constructing cationic polyelectrolyte self-assembled coating onto cellulosic fabrics - Jia-Li Yu; Wen-Yi Wang; Jia-Chi Chiou; Ka-Fu Yung; Chi-Wai Kan (Sustainable Chemistry and Pharmacy, 2025)

Finite element modeling of clavicle fracture fixations: a systematic scoping review - Yi Zheng; Jing Li; Andy Yiu-Chau Tam; Timothy Tin-Yan Lee; Yinghu Peng; James Chung-Wai Cheung; Duo Wai-Chi Wong; Ming Ni (Medical & Biological Engineering & Computing, 2025)
Finite element analysis has become indispensable for biomechanical research on clavicle fractures. This review summarized evidence regarding configurations and applications of finite element analysis in clavicle fracture fixation. Seventeen articles involving 22 clavicles were synthesized from CINAHL, Embase, IEEE Xplore, PubMed, Scopus, and Web of Science databases. Most studies investigated midshaft transverse closed fractures by reconstructing intact models from CT scans and simulating fractures through gap creation. Common loading schemes included axial compression, distal torsion, and inferior bending. The primary objective was comparing different implant designs/placements on construct stiffness, von Mises stress, and fracture site micro-motion. Our review suggested a preference for plate fixation, particularly with anterior placement, for midshaft transverse fractures. However, limited fracture types studied constrain comprehensive recommendations. Additionally, the review highlighted discrepancies between finite element and clinical studies, emphasizing the need for improved modeling of physiological conditions. Future research should focus on developing a comprehensive database of finite element models to test various implant options and placements under common loading schemes, bridging the gap between biomechanical simulations and clinical outcomes. Graphical Abstract

Ferrosilicon alloy as both reactant and catalyst for hydrogenation of SiCl4: Thermodynamics, mechanism, and kinetics studies - Zheng-Peng Wang; Zi-Yi Chi; Huai-Qiang Dou; Xue-Gang Li; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Methamphetamine and HIV-1 Tat Protein Synergistically Induce Endoplasmic Reticulum Stress to Promote TRIM13-Mediated Neuronal Autophagy - Chan Wang; Genmeng Yang; Jian Huang; Yunqing Tian; Chi-Kwan Leung; Lin Miao; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Liu Liu; Juan Li; et al. (Molecular Neurobiology, 2025)

Optimizing Cyanobacterial Biomass for Soil Restoration: Nutrient Enrichment and Microbial Modulation in Degraded Grasslands of Hulun Lake - Bingshuai Cao; Zhaoyong Zhang; Yi Tong; Qi Wang; Wenjing Li; Cuilan Wei; Chi Zang; Wenlin Wang (Bulletin of Environmental Contamination and Toxicology, 2025)

Artificial intelligence in plastic recycling and conversion: A review - Yi Fang; Yuming Wen; Leilei Dai; Chi-Hwa Wang; Siming You; Wangliang Li (Resources, Conservation and Recycling, 2025)

Effect of tertiary amine carbon quantum dots incorporation on oil/water separation performance of membranes - Gabriel V. Carballo; Hsin-Yi Lin; Pei-Chen Chen; Hong-Li Yang; Rhoda B. Leron; Chi-Lan Li; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Pathological and biochemical effects of polyethylene microplastic exposure in hydrothermal vent crab, Xenograpsus testudinatus - Mark June S. Consigna; Li-Chun Tseng; Chi Chou; Ching-Wen Huang; Yi-Ta Shao; Jiang-Shiou Hwang (Marine Pollution Bulletin, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Discovery of the dipicolinic acid synthase in the spoilage fungus Paecilomyces reveals its role in spore heat, salt, and alkaline pH resistance - Su-Yan Wang; Yun-Jiao Zhang; Li-Xiao Chen; Yi-Bo Pang; Daniela D. Herrera-Balandrano; Paul Daly; Feng-Quan Liu; Marta Filipa Simões; Xin-Chi Shi; Pedro Laborda (Food Research International, 2025)

The biodegradable poly(3-hydroxypropionate) from acrylic acid via 3-hydroxypropionic acid: Studies on catalytic hydration and self-polycondensation - Zhen-Yang Lu; Zhao Chen; Zhuo Li; Zi-Yi Chi; Xue-Gang Li; Shuang-Yu Wei; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Diffusive gradients in thin-films (DGT) for in situ measurement of neonicotinoid insecticides (NNIs) in waters - Junwu Xiong; Chang Pu; Zhe Qian; Jiapei Yi; Kang Wang; Chi Zhang; Wei Liu; Wei Chen; Li Xu; Shihua Qi; Zulin Zhang; Hao Zhang; et al. (Water Research, 2025)

Interactive mechanisms of CF3CHFCF3 with H2-CH4-air mixture explosion: A synergistic study using chemical kinetic simulation and density functional theory - Hongfu Mi; Nan Luo; Peng Shao; Hang Yi; Shuo Wang; Wenhe Wang; Yihui Niu; Ao Yang; Xinsheng Jiang; Yu Feng; Li-Huan Zhu; Chi-Min Shu (Fuel, 2025)

Nanoparticle and dialdehyde polysaccharide synergistically improving the physicochemical properties of soy protein isolate films enriched with lingonberry extract - Huan Liu; Yajun Li; Chi Zhang; Yi Yuan; Shaoyun Wang (Food Hydrocolloids, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Transcriptome and pathophysiological analysis during Bacillus cereus group infection in Pelodiscus sinensis uncovered the importance of iron and toll like receptor pathway - Li-Wu Cheng; Qiong-Yi Huang; Pei-Chi Wang; Ming-An Tsai; Shih-Chu Chen (Aquaculture, 2025)

DNA barcode reference database and gap analysis for biomonitoring Hong Kong’s marine animals - Mei-Hong Zhao; Jack Chi-Ho Ip; Chun Ming How; Yi-Xuan Li; Dumas Deconinck; Jian-Wen Qiu (Regional Studies in Marine Science, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

A novel 3D composite auxetic sandwich panel for energy absorption improvement - Yi Chao Qu; Xing Chi Teng; Yi Zhang; Wei Zhong Jiang; Meng Li Xue; Tao Xue; Jun Wen Shi; Xin Ren (Engineering Structures, 2025)

Electro-Fenton-assisted Camellia oleifera by-product composting for reduction of greenhouse gas emission and improvement of humification - Li Chen; Zhigang Yi; Yaoning Chen; Yuanping Li; Hongjuan Jiang; Jun Wang; Mengyang Zhao; Yanrong Chen; Wei Zhang; Nianping Chi; Guangming Zeng (Chemical Engineering Journal, 2025)

The patterns and controlling factors of soil carbon and nitrogen in the water level fluctuation zone of the Three Gorges Reservoir - Chenchen Wei; Yuan Qiu; Yanbing Chi; Yalong Li; Wenhao Yi; Yujie Zhou; Cheng Yan (Journal of Soils and Sediments, 2025)

ent-Kaurane diterpenoids from Isodon henryi and their anti-inflammatory activities - Yi-xiao Li; Jun Chi; Ling-xia Zhang; Fang Wang; Wei-jin Zhang; Zhi-min Wang; Li-ping Dai (Phytochemistry, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

Enhanced phosphorus removal from anoxic water using oxygen-carrying iron-rich biochar: Combined roles of adsorption and keystone taxa - Xinyan Xiong; Yi Li; Chi Zhang (Water Research, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

Bio-inspired catalysts for enhanced N₂ electroreduction to NH3: Architecting molecular screening interfaces via active sites microenvironment engineering - Xinyue Chi; Jingxian Li; Xiaoxuan Wang; Yuanyuan Xiong; Shuyuan Li; Kaixin Zhang; Zhenzhen Fu; Jiangzhou Xie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Controllable preparation of red phosphorus nanoribbons for enhanced photocatalytic degradation of Methyl Orange and Tetracycline - Jingyu Zhu; Wuhua Lv; Chi Wang; Kai Li; Yi Mei (Environmental Science and Pollution Research, 2024)

Noble metal-free plasmonic Cu/WO3-x@ZNC bi-functional composite for ciprofloxacin photocatalytic degradation and photothermal water evaporation via visible-infrared exposure - Hossam Zakaria; Yi Li; Hongyu Wei; Mohamed M. Fathy; Chi Zhang (Chemosphere, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

Enhanced high-temperature iodine capture through band-edge control in covalent organic frameworks - Yaling Zhu; Yi Li; Dan Luo; Yanlei He; Jianqiao Zhou; Dan Jiang; Xiuyun Zhang; Xiaodong Chi (Chemical Engineering Journal, 2024)

Anti-inflammatory lindenane sesquiterpenoid dimers from the roots of Chloranthus holostegius var. trichoneurus - Xiaoli Wang; Zhenyu Zan; Jun Chi; An Huang; Danyang Zhang; Houli Jiang; Yi Li; Jun Luo (Journal of Natural Medicines, 2024)

TBC1D10B promotes tumor progression in colon cancer via PAK4‑mediated promotion of the PI3K/AKT/mTOR pathway - Xiao-Jv Chi; Yi-Bei Song; Haoran Zhang; Li-Qiang Wei; Yong Gao; Xue-Jing Miao; Shu-Ting Yang; Chun-Yu Lin; Dong Lan; Xiquan Zhang (Apoptosis, 2024)

Phylogeny and genetic diversity of Echinometra sea urchin in Taiwan - Mei-Fang Lin; Ming-Che Yang; Yi-Yuan Lin; Sheng-Chi Chung; Li-Lian Liu (Marine Biology Research, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Annamiacids A and B: Two dissymmetric bis-diterpenes containing a rare ketal-γ-lactone motif from Podocarpus annamiensis and their inhibitory effects on ATP-citrate lyase - Chi Song; Ze-Yu Zhao; Jin-Xin Zhu; Yi Zang; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry Letters, 2024)

An emerging pathogen found in farm-cultured fourfinger threadfin (Eleutheronema tetradactylum), Edwardsiella piscicida, its genetic profile, virulent genes, and pathogenicity - Li-Wu Cheng; Hsien-Chung Lee; Qiong-Yi Huang; Wen-Rou Huang; Pei-Chi Wang; Shih-Chu Chen (Aquaculture, 2024)

Effects of benzophenone-3 and its metabolites on the marine diatom Chaetoceros neogracilis: Underlying mechanisms and environmental implications - Yi Yang; Guang-Jie Zhou; Ziying Li; Jiaji Sun; Alice Sze Tsai Wong; Vincent Chi Chiu Ko; Rudolf Shiu Sun Wu; Keng Po Lai (Science of The Total Environment, 2024)

Polyphenol nanoparticles based on bioresponse for the delivery of anthocyanins - Zhihuan Zang; Yuan Li; Shurui Chou; Jinlong Tian; Xu Si; Yuehua Wang; Hui Tan; Ningxuan Gao; Chi Shu; Dongnan Li; Wei Chen; Yi Chen; et al. (Food Research International, 2024)

Diet with optimal glutathione supplement improves growth, nonspecific immunity, intestinal microbiota, and antioxidant ability in Micropterus salmoides - Chuanyu Xiong; Yuyu Chi; Bei Wang; Jianhua Yi; Yongyao Yu; Yun Li; Hua Ye; Jiyuan Yin; Ronghua Wu (Journal of Fish Biology, 2024)
In this study, Micropterus salmoides were fed with dietary glutathione (GSH, 0, 100, 300, and 500 mg/kg) for 56 days to investigate its effects on growth performance, serum nonspecific immunity, liver antioxidant capacity, tissue morphology, and intestinal microbiota. The results showed that the survival rate, weight gain rate, and specific growth rate and condition factor increased, whereas the feed conversion ratio, hepato‐somatic index, and viscerosomatic index decreased in the GSH groups. Compared with the control group, the serum total protein content significantly increased, whereas the triglyceride and total cholesterol significantly decreased in the 300‐mg/kg dietary GSH group. The activities of lysozyme, alkaline phosphatase, and acid phosphatase were significantly higher in GSH‐supplemented groups, peaking at 300‐mg/kg GSH. GSH supplementation significantly increased total antioxidant capacity and decreased malondialdehyde content, with the most pronounced effects at 300‐mg/kg GSH. Further antioxidant indicators showed that a dietary supplement of 300‐mg/kg GSH significantly increased the activities of superoxide dismutase, glutathione transferase, endogenous glutathione, glutathione reductase, and catalase. At 300‐mg/kg GSH, the liver exhibited improved characteristics with alleviated vacuolation and hepatocyte nuclear shift, and intestine showed enhanced structure with increased villus height and intestinal wall thickness. Additionally, a 300‐mg/kg GSH supplementation improved the diversity of intestinal microbiota, increased the abundance of probiotics such as Bacillus, and inhibited the development of pathogenic bacteria such as Plesiomonas . Overall, the results suggest that the effect of GSH addition on improving growth performance, nonspecific immunity, antioxidant capacity, and intestinal microbiota of M. salmoides is best in the 300‐mg/kg addition group. Based on second‐degree polynomial regression analysis of weight gain, the optimum requirement of dietary GSH in M. salmoides is a 336.84‐mg/kg diet.

Cable bacteria: Living electrical conduits for biogeochemical cycling and water environment restoration - Xinyan Xiong; Yi Li; Chi Zhang (Water Research, 2024)

Mirror QCD phase transition as the origin of the nanohertz Stochastic Gravitational-Wave Background - Lei Zu; Chi Zhang; Yao-Yu Li; Yuchao Gu; Yue-Lin Sming Tsai; Yi-Zhong Fan (Science Bulletin, 2024)

DMF mineralization and substrate specificity mechanism of Aminobacter ciceronei DMFA1 - Baihui Chi; Fei Li; Xukang Wang; Haixia Pan; Xianliang Yi; Yang Liu; Jingjing Zhan; Xuwang Zhang; Hao Zhou; Wenyuan Wang (Environmental Research, 2024)

Silica-modified few-layered MoS2 for SWCNT-based thermoelectric materials - Duo Jiang; Zan Li; Yi Li; Chi Wang; Yannan Wang; Ping Fu; Yunfei Zhang; Feipeng Du (Chemical Engineering Journal, 2024)

Influence of rapid vertical mixing on bacterial community assembly in stratified water columns - Hainan Wu; Stefan Bertilsson; Yi Li; Wenlong Zhang; Lihua Niu; Wei Cai; Haibing Cong; Chi Zhang (Environmental Research, 2024)

Zwitterion grafted polyimide separator for improving lithium-ion transport and its application in LiCoO2 batteries - Haitao Huang; Kaijin Chen; Chuying Li; Zhuxin Zhou; Wenhui Wang; Bo Deng; Siwei Liu; Chao Qian; Min Yue; Zhenguo Chi; Jiarui Xu; Yi Zhang (Chemical Engineering Journal, 2024)

A proposed framework for a social-ecological traits database for studying and managing urban plants and assessing the potential of database development using Floras - Chi-Ru Chang; Mong-Huai Su; Yi-Hsuan Li; Ming-Chun Chen (Urban Forestry & Urban Greening, 2024)

Adaptation behaviors modify the effects of body fat on heat-related symptoms among Taiwanese elderly - Chi-Hsien Chen; Wen-Yi Lin; Kang-Yun Lee; Wen-Jung Sun; Li-Ying Huang; Yue-Liang Leon Guo (International Journal of Hygiene and Environmental Health, 2024)

Ammonium intercalation engineering regulated structural stability of V6O13 cathodes for durable zinc ion batteries - Ziang Wu; Jia Yao; Chi Chen; Xiang Chen; Xiaoxin Pan; Junjie Zheng; Yi Gan; Jingying Li; Xingtai Liu; Chao Xia; Lin Lv; Hao Wang; et al. (Chemical Engineering Journal, 2024)

Blue polyimides for high-performance solution-processable organic light-emitting diodes - Wenhui Wang; Kaijin Chen; Chuying Li; Faxu Lin; Yuxuan Li; Yubo Long; Juan Zhao; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang; Yuguang Ma (Chemical Engineering Journal, 2024)

Combined metabolome and transcriptome analysis reveals a critical role of lignin biosynthesis and lignification in stem-like pneumatophore development of the mangrove Avicennia marina - Yu-Chen Zhang; Li-Han Zhuang; Jia-Jie Zhou; Shi-Wei Song; Jing Li; He-Zi Huang; Bing-Jie Chi; You-Hui Zhong; Jing-Wen Liu; Hai-Lei Zheng; Xue-Yi Zhu (Planta, 2024)

Co-metabolic biodegradation of chlorinated ethene in an oxygen- and ethane-based membrane biofilm reactor - Zifang Chi; Xinyang Liu; Huai Li; Shen Liang; Yi-Hao Luo; Chen Zhou; Bruce E. Rittmann (Science of The Total Environment, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Mesocosm experimental study on sustainable riparian restoration using sediment-modified planting eco-concrete - Yi Li; Shengxiang Rong; Chi Zhang; Hongqiang Chu; Pengcheng Wei; Shiqiang Tao (Science of The Total Environment, 2023)

Superior self-cleaning surfaces via the synergy of superhydrophobicity and photocatalytic activity: Principles, synthesis, properties, and applications - Chi Zhang; Xin Zhang; Hongchen Shen; Danmeng Shuai; Xinyan Xiong; Ye Wang; Huajie Huang; Yi Li (Journal of Cleaner Production, 2023)

Facile post-treatment of PSf membranes with hexane for fractionation and concentration of alkaline textile wastewater - Yanyan Liu; Raf Dewil; Xi Zhang; Yi Li; Rilyn Todd; Mingshuo Chi; Daliang Xu; Guichuan Li; Pengrui Jin; Junfeng Zheng; Bart Van der Bruggen (Chemical Engineering Journal, 2023)

Electroacupuncture Inhibits Pain Memory and Related Anxiety-Like Behaviors by Blockading the GABAB Receptor Function in the Midcingulate Cortex - Xiaoyu Li; Yichen Zhu; Haiju Sun; Zui Shen; Jing Sun; Siqi Xiao; Xiaofen He; Boyu Liu; Yifang Wang; Yuxin Hu; Boyi Liu; Yi Liang; et al. (Molecular Neurobiology, 2023)
Pain memory is commonly considered an underlying cause of chronic pain and is also responsible for a range of anxiety. Electroacupuncture (EA) has been shown to ameliorate pain memories and exert anti-anxiety effects. Previous research has indicated that GABAergic neurons and/or GABA receptors (GABARs) in the midcingulate cortex (MCC) have potential associations with chronic pain and anxiety. However, there is no known empirical research that has specifically studied the effects of EA on the GABAergic system in the MCC. Here, we used cross-injection of carrageenan to establish the pain memory rats model. Immunofluorescence were used to detect the excitability of GABAergic neurons within MCC. Von Frey filament, elevated zero maze, and open field tests were used to measure mechanical allodynia and anxiety-like behaviors, combined with chemogenetic and pharmacologic technologies. Finally, this study provides evidence that pain memories contribute to generalized negative emotions and that downregulating the activity of GABAergic neurons within MCC could block pain memories and reverse anxiety emotion. Specifically, GABA B R is involved in pain memory and related anxiety-like behaviors. Activation of GABAergic neurons in the MCC did not reverse the effects of EA on pain memories and related anxiety-like behaviors, whereas these effects could be reversed by a GABA B R agonist. These findings highlight the functional significance of GABA B R in the EA-mediated attenuation of pain memories and related anxiety-like behaviors in rats.

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

Molecular design strategy for through-space charge transfer blue polyimides with rigid non-conjugated backbone and the role of alicyclic imide linker - Yubo Long; Kaijin Chen; Chuying Li; Wenhui Wang; Jinkun Bian; Yuxuan Li; Siwei Liu; Zhenguo Chi; Jiarui Xu; Yi Zhang (Chemical Engineering Journal, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Engineering performance and microstructure characteristics of natural marine sediment stabilized with quicklime-activated GGBS under different lime proportions - Guang-Hua Cai; Yi-Fan Zhou; Chi Sun Poon; Jiang-Shan Li (Marine Georesources & Geotechnology, 2023)

Flavonoids mitigation of typical food thermal processing contaminants: Potential mechanisms and analytical strategies - Bin Li; Jiaxin Wang; Zhen Cheng; Baoge Song; Chi Shu; Yi Chen; Wei Chen; Shufang Yang; Yiyun Yang; Jinlong Tian (Food Chemistry, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

α-amanitin induces autophagy through AMPK-mTOR-ULK1 signaling pathway in hepatocytes - Yue Xu; Shangwen Wang; Chi-Kwan Leung; Hao Chen; Chan Wang; Huijie Zhang; Shuwei Zhang; Yi Tan; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Toxicology Letters, 2023)

Plasmon driven super-high HER activity of electronic structure and lattice strain engineered single atomic layer Pd@Au nanorods - Yi-Bai Sun; Miao Ni; Chen Chi; Dong-Rui Yang; Xue-Lu Chen; Qi Qi; Jian Li; Xing-Hua Xia (Chemical Engineering Journal, 2023)

TiO2/BP/g-C3N4 heterojunction photocatalyst for the enhanced photocatalytic degradation of RhB - Shujian Liu; Yanqing Ge; Chi Wang; Kai Li; Yi Mei (Environmental Science and Pollution Research, 2023)

Quality of life and cost-effectiveness of different breast cancer surgery procedures: a Markov decision tree-based approach in the framework of Predictive, Preventive, and Personalized Medicine - Hon-Yi Shi; Chiu-Hui Li; Yen-Chen Chen; Chong-Chi Chiu; Hao-Hsien Lee; Ming-Feng Hou (EPMA Journal, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

The characteristic evolution and formation mechanism of hybrid microalgae biofilm and its application in mariculture wastewater treatment - Yanbo Liu; Guoyu Zhang; Weirun Li; Yi Ding; Hong You; Jing Zhu; Haoran Leng; Chi Xu; Xiaodi Xing; Jingyue Xu; Zhipeng Li (Journal of Environmental Chemical Engineering, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Water quality improvement and consequent N2O emission reduction in hypoxic freshwater utilizing green oxygen-carrying biochar - Xinyan Xiong; Yi Li; Chi Zhang; Xinyi Zhou (Science of The Total Environment, 2023)

Photodegradation behavior and mechanism of dibutyl phthalate in water under flood discharge atomization - Li Lin; Sheng Zhang; Lei Dong; Yueqi Cao; Wei Zhang; Xiong Pan; Yi Li; Chi Zhang; Jingxiang Tao; Di Jia; John Crittenden (Science of The Total Environment, 2023)

Dynamic risk analysis of oil depot storage tank failure using a fuzzy Bayesian network model - Qing-Yun Zhou; Bei Li; Yi Lu; Jie Chen; Chi-Min Shu; Ming-shu Bi (Process Safety and Environmental Protection, 2023)

Emestrin-type thiodiketopiperazines from Aspergillus nidulans SD-531, a fungus obtained from the deep-sea sediment of cold seep in the South China Sea - Feng-Yi Lv; Attila Mándi; Xiao-Ming Li; Lu-Ping Chi; Xin Li; Bin-Gui Wang; Tibor Kurtán; Ling-Hong Meng (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

Cyanidin-3- O -glucoside and its phenolic metabolites ameliorate intestinal diseases via modulating intestinal mucosal immune system: potential mechanisms and therapeutic strategies - Zhen Cheng; Xu Si; Hui Tan; Zhihuan Zang; Jinlong Tian; Chi Shu; Xiyun Sun; Zhiying Li; Qiao Jiang; Xianjun Meng; Yi Chen; Bin Li; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Metagenomic insights into the effects of benzyl dodecyl dimethyl ammonium bromide (BDAB) shock on bacteria-driven nitrogen removal in a moving-bed biofilm reactor (MBBR) - Jing Wang; Ling Li; Baihui Chi; Jiajia Shan; Xianliang Yi; Yang Liu; Hao Zhou (Chemosphere, 2023)

A novel BC/g-C3N4 porous hydrogel carrier used in intimately coupled photocatalysis and biodegradation system for efficient removal of tetracycline hydrochloride in water - Huanjun Zhang; Yanan Yu; Yi Li; Li Lin; Chi Zhang; Wenlong Zhang; Longfei Wang; Lihua Niu (Chemosphere, 2023)

Methane emission mitigation in hypoxic freshwater triggered by oxygen-carrying dual-modified sediment-based biochar - Xinyan Xiong; Yi Li; Xinyi Zhou; Chi Zhang (Journal of Cleaner Production, 2023)

Ecological risk assessment and corrective actions for dioxin-polluted sediment in a chemical plant's brine water storage pond - Chi-Wei Huang; Wen-Yen Huang; Chitsan Lin; Yi-Lin Li; Tsung-Po Huang; Xuan-Thanh Bui; Huu Hao Ngo (Science of The Total Environment, 2023)

Seasonal influence on pollution index and risk of multiple compositions of microplastics in an urban river - Chi-Wei Huang; Yi-Lin Li; Chitsan Lin; Xuan-Thanh Bui; Thi-Dieu-Hien Vo; Huu Hao Ngo (Science of The Total Environment, 2023)

A combined precipitation-adsorption method for harmless treatment of glyphosate mother liquor - Zhanhui Li; Yi Wang; Ruyi Zhou; Junxia Yu; Xiaodi Li; Chunqiao Xiao; Haobo Hou; Ruan Chi; Guoqing Feng (Journal of Cleaner Production, 2023)

Composite K/Cu/Ni hexacyanoferrates embedded biomass straw for cesium removal - Xiaoyu Li; Yingwei Xiong; Fangting Chi; Yumin Huang; Zhe Wang; Facheng Yi (Bioresource Technology Reports, 2023)

One-step self-assembly of multilayer graphene oxide via streamlined click reactions for sensitive colorimetric assays - Yanfeng Gao; Yanping Wang; Xinli Liu; Zhenxing Zhu; Zhun Li; Zhibin Zhang; Yi Yin; William Chi Shing Cho; Yujun Song; Yuzhen Wang (Analytica Chimica Acta, 2023)

A novel TiO2-x/TiN@ACB composite for synchronous photocatalytic Cr(VI) reduction and water photothermal evaporation under visible/infrared light illumination - Hossam Zakaria; Yi Li; Mohamed M. Fathy; Xinyi Zhou; Xinyan Xiong; Ye Wang; Shengxiang Rong; Chi Zhang (Chemosphere, 2023)

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Continuous inactivation of human adenoviruses in water by a novel g-C3N4/WO3/biochar memory photocatalyst under light-dark cycles - Chi Zhang; Wei Xiong; Yi Li; Li Lin; Xinyi Zhou; Xinyan Xiong (Journal of Hazardous Materials, 2023)

Rare disperse elements in epithermal deposit: Insights from LA–ICP–MS study of sphalerite at Dalingkou, South China - Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Guo-Guang Wang; Jun-Ying Ding; Shu-Wu Chu; Wen-Sheng Li; Wen-Qing Huang; Ren-Zhi Zhu; Zhe Chi (Journal of Geochemical Exploration, 2023)

Thermal behavior, synergistic effect and thermodynamic parameter evaluations of biomass/plastics co–pyrolysis in a concentrating photothermal TGA - Abdulmajid Abdullahi Shagali; Song Hu; Hanjian Li; Huanying Chi; Haoran Qing; Jun Xu; Long Jiang; Yi Wang; Sheng Su; Jun Xiang (Fuel, 2023)

Ethane-driven chromate and nitrate bioreductions in a membrane biofilm reactor - Zifang Chi; Shijie Ju; Wenjing Wang; Huai Li; Yi-Hao Luo; Bruce E. Rittmann (Chemical Engineering Journal, 2023)

Low concentrations of benzophenone-type UV-filters impair testis development in the amphibian Xenopus laevis - Hong-Mei Li; Ying-Chi Zhang; Yuan-Yuan Li; Qing-Qing Zhu; Jie Li; Hai-Ming Xu; Yi-Ming Xiong; Zhan-Fen Qin (Aquatic Toxicology, 2023)

Investigations on Cutting Force and Temperature Field of Pick Cutter Based on Single Factor and Orthogonal Test Methods - Long-Chuan Deng; Xiao-Zhao Li; Yi-Wei Chen; Qian-Wei Zhuang; Long-Hai Zhu; Chi Zhang (Rock Mechanics and Rock Engineering, 2023)

Role of low-frequency wind variability in inducing WWBs during the onset of super El Niños - Yi-Kai Wu; Chi-Cherng Hong; Tim Li; An-Yi Huang (Climate Dynamics, 2023)

Role of Sp1 in atherosclerosis - Jie-Feng Jiang; Zheng-Yang Zhou; Yi-Zhang Liu; Li Wu; Bin-Bin Nie; Liang Huang; Chi Zhang (Molecular Biology Reports, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

Shoal-to-Strata Ratio Technique and Its Use in Describing Carbonate Rock Sedimentary Facies in the Eastern Sichuan Basin - Xiuquan Hu; Hong Liu; Xiucheng Tan; Chenjing Xiao; Qian Tan; Jianghan Li; Chi Yi (Journal of Marine Science and Engineering, 2022)
The requirements for the accurate characterization of shoal sediments have increased in view of the fact that strata are eroded due to uplift and it is difficult to calculate the real thickness of granular shoal. To solve this problem, with the shoal-to-strata ratio, the type and distribution range of carbonate rock shoal facies are described, and the characterization of sedimentary facies is subsequently presented. Taking the P2m2a in Eastern Sichuan as an example, the following conclusions were obtained. (1) The primary rock types of the shoal facies of the P2m2a are bioclastic limestone and micrite limestone. The logging facies of platform margin shoals, intra-platform high-energy shoals, intra-platform low-energy shoals, and sloping low-energy shoals are large funnel-type, small funnel-type, box-type, and finger-like, respectively. The platform margin shoals and intra-platform high-energy shoals are imbricate seismic facies, and the intra-platform low-energy shoals and sloping low-energy shoals are S-type progradation seismic facies and oblique progradation. (2) The shoal-to-strata ratio of platform margin shoals is the highest, followed by intra-platform high-energy shoals, intra-platform low-energy shoals, and sloping low-energy shoals. (3) Shoal facies deposits have a certain controlling effect on gas production, and platform margin shoals have greater exploration potential. (4) This example shows that in the areas where carbonate rock strata are eroded, compared with the method of characterizing the sedimentary facies of carbonate rock using the shoal thickness, the shoal-to-strata ratios are more accurate. (5) The planar distribution diagram of the shoal-to-strata ratio can be used as a supporting map for compiling sedimentary facies maps. This method is worth applying in related research fields.

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Genomic characterization of a rare Carica papaya X chromosome mutant reveals a candidate monodehydroascorbate reductase 4 gene involved in all-hermaphrodite phenomenon - Jen-Ren Chen; Hiroki Ueno; Hideo Matsumura; Naoya Urasaki; Chen-Yu Lee; Fure-Chyi Chen; Shih-Wen Chin; Chun-Chi Liu; Chan-Tai Chiu; Kazuhiko Tarora; Jing-Yi Li; Chieh Ying Lee; et al. (Molecular Genetics and Genomics, 2021)

Heat stress inhibits TLR4-NF-κB and TLR4-TBK1 signaling pathways in broilers infected with Salmonella Typhimurium - Wei-Hao Li; Yi-Lei Liu; Jian-Chi Lun; Yong-Ming He; Lu-Ping Tang (International Journal of Biometeorology, 2021)
With the global warming, the harm of heat stress (HS) to the breeding industry has become more common, which causes the decline of animal production performance and low immunity. This study aimed to analyze the effect of HS on the intestinal immune function of Salmonella- infected chickens. Fourteen-day-old broilers were divided into the following four groups of eight replicates: control (Control), heat stress (HS), Salmonella Typhimurium (ST), and heat stress + Salmonella Typhimurium (HS+ST). The broilers were subjected to a heat stress of 35 °C from 15 to 28 days of age. Salmonella Typhimurium (ST, 14028, 10 9 cfu/mL) was inoculated, via oral administration at 29 days of age, into ST and HS+ST group birds. On the 4th day after Salmonella Typhimurium administration, an increase in jejunum IgA levels was observed in chickens infected with Salmonella Typhimurium. Mechanistic regulation of TLR4-NFκB-NLRP3 and TLR4-TBK1 signaling by heat stress was evaluated in Salmonella Typhimurium–infected broilers. Heat stress markedly inhibited the expression of cytokines including TNF-α, IL-6, IL-1β, NLRP3, caspase-1, NF-κB-p65, and p-NF-κB-p65, and the TLR4-TBK1 cytokines IFN-α, IFN-γ, p-IRF3, and p-TBK1 in jejunum of broilers infected with Salmonella Typhimurium. Collectively, our results demonstrate that heat stress can inhibit intestinal immune response by downregulating the expression of TLR4-NFκB-NLRP3 and TLR4-TBK1 signaling pathways in broilers infected with Salmonella Typhimurium.

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Projected changes in the characteristics of the East Asian summer monsoonal front and their impacts on the regional precipitation - Yana Li; Ngar-Cheung Lau; Chi-Yung Tam; Ho-Nam Cheung; Yi Deng; Henian Zhang (Climate Dynamics, 2021)

High-Level Expression and Purification of Melittin in Escherichia coli Using SUMO Fusion Partner - Qiu-chi Chen; Lei Liu; Tian-Yi Yu; Lu Tang; Mo-li Yin; Wen-he Zhu; Xiu-yun Jiang; Hui-yan Wang (International Journal of Peptide Research and Therapeutics, 2021)

Latitudinal differences in early growth of largehead hairtail ( Trichiurus japonicus ) in relation to environmental variables - Peng Sun; Qi Chen; Caihong Fu; Yi Xu; Runlong Sun; Jianchao Li; Haiqing Yu; Chi Zhang; Yang Liu; Zhenjiang Ye; Yongjun Tian; Mikko Heino (Fisheries Oceanography, 2020)
Largehead hairtail ( Trichiurus japonicus ) in the China Seas shows an increasing catch trend, despite continued overexploitation, which could be attributed to improved recruitment as a result of strengthened early growth. To understand the early growth variability of largehead hairtail, we examined the linkages between early growth, as revealed by otolith microstructure, and the associated environmental variables over both spatial and temporal scales. Young‐of‐the‐Year largehead hairtail were collected from three regions in the Bohai, Yellow and East China Seas between 29° and 39° N. Daily increment widths of sagittal otoliths were measured and used as a proxy for somatic growth. We found two spawning cohorts, Spring‐ and Summer‐spawned cohorts, that showed latitudinal differences in both mean growth and growth pattern. The transition time from larval to juvenile stage was identified at around 40 days. Daily increment widths of two cohorts showed similar growth pattern in the first 40 days, while location had a marked effect on daily growth over 41–110 days. This suggests physiologically constrained growth pattern in larval stage, but more plastic growth subject to habitat‐specific influences in juvenile stage. The gradient forest analysis identified sea bottom temperature, vertical temperature gradient, and sea surface salinity, as the most important variables in determining early growth. Latitudinal differences in early growth pattern and their response to environmental variables suggest adaptive plasticity of early growth, which has notable implication for the management and sustainable utilization of this important but heavily exploited resource in the China Seas.

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

A novel hydroxofluorographene-coated melamine foam for efficient and repeatable oil removal from water - Xinyi Zhou; Yi Li; Chi Zhang; Yuming Wang; Yumiao Lu (Environmental Science and Pollution Research, 2020)

Enhanced adsorption of hydrophobic organic contaminants by high surface area porous graphene - Lixuan Ma; Kai Li; Chi Wang; Bo Liu; Hongbo Peng; Yi Mei; Ping Ning (Environmental Science and Pollution Research, 2020)

Applying Iterative Method to Solving High-Order Terms of Seafloor Topography - Diao Fan; Shanshan Li; Shuyu Meng; Yi Lin; Zhibin Xing; Chi Zhang; Junjun Yang; Xiaoyun Wan; Zhenhao Qu (Marine Geodesy, 2020)

The effect of polystyrene plastics on the toxicity of triphenyltin to the marine diatom Skeletonema costatum—influence of plastic particle size - Xianliang Yi; Jianfeng Wang; Zhaochuan Li; Zherui Zhang; Tongtong Chi; Miao Guo; Wentao Li; Hao Zhou (Environmental Science and Pollution Research, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Preparation of AgCl/TNTs nanocomposites for organic dyes and inorganic heavy metal removal - Cheng-Yen Tsai; Chen-Wuing Liu; Hsing-Cheng Hsi; Kuen-Song Lin; Yi-Wen Lin; Li-Chi Lai; Tsung-Nan Weng (Environmental Science and Pollution Research, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Effect of Multi-walled Carbon Nanotubes on the Toxicity of Triphenyltin to the Marine Copepod Tigriopus japonicus - Xianliang Yi; Mingyue Yu; Zhaochuan Li; Tongtong Chi; Siyuan Jing; Keke Zhang; Wentao Li; Minghuo Wu (Bulletin of Environmental Contamination and Toxicology, 2019)

Combined effect of polystyrene plastics and triphenyltin chloride on the green algae Chlorella pyrenoidosa - Xianliang Yi; Tongtong Chi; Zhaochuan Li; Jianfeng Wang; Mingyue Yu; Minghuo Wu; Hao Zhou (Environmental Science and Pollution Research, 2019)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

A Novel Approach to Utilize Icariin as Icariin-Derived ECM on Small Intestinal Submucosa Scaffold for Bone Repair - Mei Li; Chi Zhang; Yi Zhong; Jiyuan Zhao (Annals of Biomedical Engineering, 2017)

Assessment of germling ability of the introduced marine brown alga, Sargassum horneri, in Northern Taiwan - Showe-Mei Lin; Roger Huang; Hisao Ogawa; Li-Chia Liu; Yi-Chi Wang; Yushan Chiou (Journal of Applied Phycology, 2017)

Association of lead exposure with cardiovascular risk factors and diseases in Chinese adults - Chi Chen; Qin Li; Xiaomin Nie; Bing Han; Yi Chen; Fangzhen Xia; Hualing Zhai; Ningjian Wang; Yingli Lu (Environmental Science and Pollution Research, 2017)

Dosage effects of ZP2 and ZP3 heterozygous mutations cause human infertility - Wenqiang Liu; Kunming Li; Dandan Bai; Jiqing Yin; Yuanyuan Tang; Fengli Chi; Linfeng Zhang; Yu Wang; Jiaping Pan; Shanshan Liang; Yi Guo; Jingling Ruan; et al. (Human Genetics, 2017)

The effect of Fe-Mn minerals and seawater interface and enrichment mechanism of ore-forming elements of polymetallic crusts and nodules from the South China Sea - Yao Guan; Xiaoming Sun; Xiaodong Jiang; Rina Sa; Li Zhou; Yi Huang; Yating Liu; Xiaojie Li; Rongfei Lu; Chi Wang (Acta Oceanologica Sinica, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Basinwide disaster loss assessments under extreme climate scenarios: a case study of the Kaoping River basin - Hsin-Chi Li; Tingyeh Wu; Hsiao-Ping Wei; Hung-Ju Shih; Yi-Chiung Chao (Natural Hazards, 2017)

Influence of climate regime shift on the interdecadal change in tropical cyclone activity over the Pacific Basin during the middle to late 1990s - Chi-Cherng Hong; Yi-Kai Wu; Tim Li (Climate Dynamics, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Blood Cadmium Level Associates with Lower Testosterone and Sex Hormone-Binding Globulin in Chinese men: from SPECT-China Study, 2014 - Chi Chen; Ningjian Wang; Xiaomin Nie; Bing Han; Qin Li; Yi Chen; Hualing Zhai; Chunfang Zhu; Yingchao Chen; Fangzhen Xia; Meng Lu; Dongping Lin; et al. (Biological Trace Element Research, 2016)

Human cytomegalovirus UL49 encodes an early, virion-associated protein essential for virus growth in human foreskin fibroblasts - Feng Zhu; Jian Yuan; Hong-Jian Li; Zhi-Feng Zeng; Zhi-Wen Luo; Shi-Qian Li; Chi-Qiang He; Xue-Fang Jia; Xin Zhang; Hui Zuo; Yi-Min Liu; Martin Chang; et al. (Archives of Virology, 2016)

Strong and stable geographic differentiation of swamp buffalo maternal and paternal lineages indicates domestication in the China/Indochina border region - Yi Zhang; Yongfang Lu; Marnoch Yindee; Kuan‐Yi Li; Hsiao‐Yun Kuo; Yu‐Ten Ju; Shaohui Ye; Md Omar Faruque; Qiang Li; Yachun Wang; Vu Chi Cuong; Lan Doan Pham; et al. (Molecular Ecology, 2016)
The swamp type of the Asian water buffalo is assumed to have been domesticated by about 4000 years BP , following the introduction of rice cultivation. Previous localizations of the domestication site were based on mitochondrial DNA (mt DNA ) variation within China, accounting only for the maternal lineage. We carried out a comprehensive sampling of China, Taiwan, Vietnam, Laos, Thailand, Nepal and Bangladesh and sequenced the mt DNA Cytochrome b gene and control region and the Y‐chromosomal ZFY , SRY and DBY sequences. Swamp buffalo has a higher diversity of both maternal and paternal lineages than river buffalo, with also a remarkable contrast between a weak phylogeographic structure of river buffalo and a strong geographic differentiation of swamp buffalo. The highest diversity of the swamp buffalo maternal lineages was found in south China and north Indochina on both banks of the Mekong River, while the highest diversity in paternal lineages was in the China/Indochina border region. We propose that domestication in this region was later followed by introgressive capture of wild cows west of the Mekong. Migration to the north followed the Yangtze valley as well as a more eastern route, but also involved translocations of both cows and bulls over large distances with a minor influence of river buffaloes in recent decades. Bayesian analyses of various migration models also supported domestication in the China/Indochina border region. Coalescence analysis yielded consistent estimates for the expansion of the major swamp buffalo haplogroups with a credibility interval of 900 to 3900 years BP . The spatial differentiation of mt DNA and Y‐chromosomal haplotype distributions indicates a lack of gene flow between established populations that is unprecedented in livestock.

A novel enterocin T1 with anti-Pseudomonas activity produced by Enterococcus faecium T1 from Chinese Tibet cheese - Hui Liu; Lanwei Zhang; Huaxi Yi; Xue Han; Wei Gao; Chunliang Chi; Wei Song; Haiying Li; Chunguang Liu (World Journal of Microbiology and Biotechnology, 2016)

Occurrence of endocrine disrupting compounds in aqueous environment and their bacterial degradation: A review - Chi Zhang; Yi Li; Chao Wang; Lihua Niu; Wei Cai (Critical Reviews in Environmental Science and Technology, 2016)

Conditional Probabilities for Large Events Estimated by Small Earthquake Rate - Yi-Hsuan Wu; Chien-Chih Chen; Hsien-Chi Li (Pure and Applied Geophysics, 2016)

Ag@helical chiral TiO2 nanofibers for visible light photocatalytic degradation of 17α-ethinylestradiol - Chi Zhang; Yi Li; Dawei Wang; Wenlong Zhang; Qing Wang; Yuming Wang; Peifang Wang (Environmental Science and Pollution Research, 2015)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Combined effects of the BDNF rs6265 (Val66Met) polymorphism and environment risk factors on psoriasis vulgaris - Cheng Quan; Kun-Ju Zhu; Chi Zhang; Zhong Liu; Huan Liu; Cheng-Yao Zhu; Ke-Shen Li; Yi-Ming Fan; Jie Zheng (Molecular Biology Reports, 2014)

Sensitivity analysis of the hydrological response of the Gaping River basin to radar-raingauge quantitative precipitation estimates - Tsung-yi Pan; Meng-ying Li; Yong-jun Lin; Tsang-jung Chang; Jihn-sung Lai; Yih-chi Tan (Hydrological Sciences Journal, 2014)

The climate regime shift over the Pacific during 1996/1997 - Chi-Cherng Hong; Yi-Kai Wu; Tim Li; Chih-Chun Chang (Climate Dynamics, 2014)

Functional study on the mutations in the silkworm (Bombyx mori) acetylcholinesterase type 1 gene (ace1) and its recombinant proteins - Ju-mei Wang; Bin-bin Wang; Yi Xie; Shan-shan Sun; Zhi-ya Gu; Lie Ma; Fan-chi Li; Yi-fan Zhao; Bin Yang; Wei-de Shen; Bing Li (Molecular Biology Reports, 2014)

Molecular characterization of the full-length L and M RNAs of Tomato yellow ring virus, a member of the genus Tospovirus - Tsung-Chi Chen; Ju-Ting Li; Ya-Shu Fan; Yi-Chun Yeh; Shyi-Dong Yeh; Richard Kormelink (Virus Genes, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

A Critical Review on Life Cycle Assessment Studies of Diapers - Frency Sau-Fun Ng; Subramanian Senthilkannan Muthu; Yi Li; Patrick Chi-Leung Hui (Critical Reviews in Environmental Science and Technology, 2013)

Anti-human hepatoma Hep-G2 proliferative, apoptotic, and antimutagenic activity of tagitinin C from Tithonia diversifolia leaves - May-Hua Liao; Yuan-Nuan Tsai; Chi-Yu Yang; Chi-Long Juang; Ming-Yi Lee; Li-Hsueh Chang; Hsiao-Chuan Wen (Journal of Natural Medicines, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Combretastatin A-4 derivatives: synthesis and evaluation of 2,4,5-triaryl-1H-imidazoles as potential agents against H1299 (non-small cell lung cancer cell) - Chih-Hua Tseng; Chi-Yi Li; Chien-Chih Chiu; Huei-Ting Hu; Chein-Hwa Han; Yeh-Long Chen; Cherng-Chyi Tzeng (Molecular Diversity, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Environmental assessment of polycyclic aromatic hydrocarbons in the surface sediments of a remote region on the eastern coast, Taiwan - Jun-Yi Kuo; Fung-Chi Ko; Jing-O Cheng; Pei-Jie Meng; Jan-Jung Li; Chin-Chang Hung (Environmental Monitoring and Assessment, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Possible roles of auxin and zeatin for initiating the dwarfing effect of M9 used as apple rootstock or interstock - Hong Li Li; He Zhang; Chi Yu; Li Ma; Yi Wang; Xin Zhong Zhang; Zhen Hai Han (Acta Physiologiae Plantarum, 2012)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Complete genomic sequence of watermelon bud necrosis virus - Ju-Ting Li; Yi-Chun Yeh; Shyi-Dong Yeh; Joseph A. J. Raja; Prem A. Rajagopalan; Lu-Yuan Liu; Tsung-Chi Chen (Archives of Virology, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Recurrent Cerebellar Hemorrhage: Case Report and Review of the Literature - Yung-Tsan Wu; Ming-Fu Hsieh; Heng-Yi Chu; Shao-Chi Lu; Shin-Tsu Chang; Tsung-Ying Li (The Cerebellum, 2010)

China’s wetland change (1990–2000) determined by remote sensing - Peng Gong; ZhenGuo Niu; Xiao Cheng; KuiYi Zhao; DeMin Zhou; JianHong Guo; Lu Liang; XiaoFeng Wang; DanDan Li; HuaBing Huang; Yi Wang; Kun Wang; et al. (Science China Earth Sciences, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

NMDA receptor antagonist MK-801 reduces neuronal damage and preserves learning and memory in a rat model of traumatic brain injury - Rui-Zhang Han; Jin-Jia Hu; Yuan-Chi Weng; Ding-Feng Li; Yi Huang (Neuroscience Bulletin, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

A population-based, case–control study of green tea consumption and leukemia risk in southwestern Taiwan - Yau-Chang Kuo; Chu-Ling Yu; Chen-Yu Liu; Su-Fen Wang; Pi-Chen Pan; Ming-Tsang Wu; Chi-Kung Ho; Yu-Shing Lo; Yi Li; David C. Christiani (Cancer Causes & Control, 2009)

Neuronal dysfunction of a long projecting multisynaptic pathway in response to methamphetamine using manganese-enhanced MRI - Yi-Hua Hsu; Chiao-Chi V. Chen; Anil Zechariah; Cecil C. Yen; Li-Chuan Yang; Chen Chang (Psychopharmacology, 2008)

Responses of Helicoverpa armigera to Tomato Plants Previously Infected by ToMV or Damaged by H. armigera - Li Lin; Tse-Chi Shen; Yi-Hua Chen; Shaw-Yhi Hwang (Journal of Chemical Ecology, 2008)

Isolation and characterization of the zebrafish Danio rerio insulin-like growth factor binding protein-3 promoter region - Ming Jun CHOU; Jian Chyi CHEN; Jyh Yih CHEN; Hong Yi GONG; Li Tzu LI; Tzou Chi HUANG; Jen Leih WU; Ching Ming KUO (Fisheries Science, 2008)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Human Multidrug Resistance Associated Protein 4 Confers Resistance to Camptothecins - Quan Tian; Jing Zhang; Theresa May Chin Tan; Eli Chan; Wei Duan; Sui Yung Chan; Urs Alex Boelsterli; Paul Chi-Lui Ho; Hongyuan Yang; Jin-Song Bian; Min Huang; Yi-Zhun Zhu; et al. (Pharmaceutical Research, 2005)

St. John’s Wort Modulates the Toxicities and Pharmacokinetics of CPT-11 (Irinotecan) in Rats - Zeping Hu; Xiaoxia Yang; Paul Chi-Liu Ho; Eli Chan; Sui Yung Chan; Congjian Xu; Xiaotian Li; Yi-Zhun Zhu; Wei Duan; Xiao Chen; Min Huang; Hongyuan Yang; et al. (Pharmaceutical Research, 2005)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

A new role of heparin: A polysaccharide for gastrointestinal diseases - Yi N. Ye; Yang Li; Marcel W. L. Koo; Chi H. Cho (Inflammopharmacology, 2002)